Designing an Observing System to Study the Surface Biology and Geology (SBG) of the Earth in the 2020s. Issue 1 (18th January 2023) - Stavros, E. Natasha; Chrone, Jon; Cawse‐Nicholson, Kerry; Freeman, Anthony; Glenn, Nancy F.; Guild, Liane; Kokaly, Raymond; Lee, Christine; Luvall, Jeffrey; Pavlick, Ryan; Poulter, Benjamin; Schollaert Uz, Stephanie; et al.
Abstract: Observations of planet Earth from space are a critical resource for science and society. Satellite measurements represent very large investments and United States (US) agencies organize their effort to maximize the return on that investment. The US National Research Council conducts a survey of Earth science and applications to prioritize observations for the coming decade. The most recent survey prioritized a visible to shortwave infrared imaging spectrometer and a multispectral thermal infrared imager to meet a range of needs for studying Surface Biology and Geology (SBG). SBG will be the premier integrated observatory for observing the emerging impacts of climate change by characterizing the diversity of plant life and resolving chemical and physiological signatures. It will address wildfire risk, behavior, and recovery as well as responses to hazards such as oil spills, toxic minerals in minelands, harmful algal blooms, landslides, and other geological hazards. The SBG team analyzed needed instrument characteristics (spatial, temporal, and spectral resolutions, measurement uncertainty) and assessed the cost, mass, power, volume, and risk of different architectures. We present an overview of the Research and Applications trade‐study analysis of algorithms, calibration and validation needs, and societal applications with specifics of substudies detailed in other articles in this special collection. We provide a value framework to converge from hundreds down to three candidate architectures recommended for development. The analysis identified valuable opportunities for international collaboration to increase the revisit frequency, adding value for all partners, leading to a clear measurement strategy for an observing system architecture. Plain Language Summary: We present the observing system science, applications, and measurement objectives for studying the Earth's Surface Biology and Geology with a global visible to shortwave infrared imaging spectrometer and a multispectral thermal infrared imager as part of the NASA Earth System Observatory slated for launch in the late 2020s. This mission will enable interdisciplinary science relevant to studying the biology and geology of the Earth's surface unlike any other mission before. Measurements are relevant for studying snow and ice, mineralogy, volcanology, biology, ecology, and components of radiative forcing from the surface such as greenhouse gas emissions. The observations not only have scientific value in studying feedbacks and interactions of surface processes (e.g., wildfire) but also are invaluable to supporting real‐world decision making such as water conservation, agriculture crop classification, forest health, and many others. The work presented here outlines the study conducted over 3 years that informed an architecture study to design a satellite observing system to provide the most value for science and applications as possible. Key Points: Spectroscopic and thermal observations will provide unprecedented information of the Earth's Surface Biology and Geology As part of the NASA Earth System Observatory, these observations will transform Earth science and environmental management This study informed mission design constraints to provide observations of value for science and decision‐making applications